IMPLEMENTASI PARTISIPASI MASYARAKAT DALAM PROSES PEMBAHASAN DAN PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA DPRD PROVINSI JAMBI - Masriyani Masriyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Mandated in the local government law as stipulated in Article 354, that opened space for public participation in the implementation of local government for the realization of a good government. In this paper will be described how the importance of community participation in theory view and how the implementation of community participation, especially in the discussion and determination of regional expenditure budget in Jambi province. It is concluded that theoretically, community participation has an important influence in the formation of a rule of law. The importance of this participation is due to the mixing of political interests in local government. So the law or rules produced will bring the public interest, not a certain political pressure. In the discussion and stipulation of the regional expenditure budget on the legislative council, although it has been regulated by Act No 23 of 2014, and in the DPRD  Code of Conduct, it has not yet been optimally implemented. Because the participation of the community is done only limited listening without any initiative to request ideas, suggestions or anspirasi community leaders presented at the hearing with opinions. It is therefore recommended that further regulation be established on the mechanism of implementation of community participation in the establishment of every legal product in the region. So it has a groove and procedures and legal umbrella that has legal certainty.Keyword: Participate of citizen in law making process